Community Structure of Leaf-Litter Ants in a Neotropical Dry Forest: A Biogeographic Approach to Explain Betadiversity - Rogério Silvestre; Manoel F. Demétrio; Jacques H. C. Delabie (Psyche: A Journal of Entomology)
This paper describes habitat and geographic correlates of ant diversity in Serra da Bodoquena, a poorly surveyed region of central-western Brazil. We discuss leaf-litter ant diversity on a regional scale, with emphasis on the contribution of each of the processes that form the evolutionary basis of contemporary beta diversity. The diversity of leaf-litter ants was assessed from a series of 262 Winkler samples conducted in two microbasins within a deciduous forest domain. A total of 170 litter-dwelling ant species in 45 genera and 11 subfamilies was identified. The data showed that the study areas exhibited different arrangements of ant fauna, with a high turnover in species composition between sites, indicating high beta diversity. Our analysis suggests that the biogeographic history of this tropical dry forest in the centre of South America could explain ant assemblage structure more than competitive dominance. The co-occurrence analysis showed that species co-occur less often than expected by chance in only two of the localities, suggesting that, for most of the species, co-occurrences are random. The assessment of the structure of the diversity of litter-dwelling ants is the first step in understanding the beta diversity patterns in this region of great biogeographic importance.